Genetic characteristic of giant featherback, Chitala lopis (Bleeker, 1851) from Lampung and Kalimantan using COI Gene - Alam Putra Persada; Dedy Duryadi Solihin; Ridwan Affandi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
DNA barcoding based on partial Cytochrome Oxidase subunit I (COI) gene in the mitochondrial has widely used in species identification and biodiversity studies. COI gene application is expected to obtain genetic characteristic, genetic variations and phylogeny of giant featherback. The aim of this research was to analyze genetic diversity of giant featherback Chitala lopis in Lampung and Kalimantan. To analyse genetic distance, Kimura two parameter (K2P) model was performed where to determine nucleotide variation & polymorphism and also reconstructed of phylogenetic tree was used MEGA 7.0 software. Total nine individuals were obtained from three populations, i.e. Lampung, West Kalimantan and South Kalimantan. The results showed that giant featherback has 689 bp conserve, 18 bp variation, 13 bp parsimony-informative, and 2 bp singleton sites from 707 bp COI partial gene. The average within-species, in-group, and out-group based on K2P distances were 1.24%, 1.43% & 1.58% (AP008922.1; KM213054.1), and 13.00% respectively. The Single Nucleotide Polymorphism (SNP) was obtaining from 13 SNP sites. West Kalimantan samples have two SNP (471 and 528 site). The South Kalimantan samples showed more specific nucleotides with nine SNP (120, 129, 144, 201, 306, 324, 474, 615 and 644). Based on genetic distance, the biggest difference was in the South Kalimantan sample (1.58%) compared with Lampung and West Kalimantan. The results of the K2P neighbour-joining phylogenetic tree reconstruction show that the South Kalimantan samples are in a different group. The West Kalimantan sample shows that it is closely related to the Lampung. Abstrak Barkoding DNA berdasarkan gen parsial Cytochrome Oxidase subunit I (COI) mitokondria telah banyak digunakan pada identifikasi spesies dan studi biodiversitas. Penggunaan gen COI mampu memperoleh karakteristik genetik, variasi genetik, dan filogeni. Tujuan penelitian ini adalah menganalisis keragaman genetik spesies ikan belida Chitala lopis asal Lampung dan Kalimantan. Analisis yang digunakan yaitu menghitung jarak genetik dengan model Kimura two parameter (K2P), melihat variasi nukleotida, polimorfisme dan merekonstruksi pohon filogenetik menggunakan software MEGA 7.0. Sebanyak sembilan individu ikan belida dikoleksi dari tiga populasi yaitu: Lampung, Kalimantan Barat dan Kalimantan Selatan. Hasil analisis urutan nukleotida yang didapat menunjukkan 689 pb situs konservatif, 18 pb situs variasi, 13 pb situs parsimoni, dan 2 pb situs singleton dari 707 pb gen parsial COI. Jarak rata-rata intraspesies, ingroup, outgroup berdasarkan K2P adalah 1,24%, 1,43% & 1,58% (Kode akses Genbank: AP008922.1; KM213054.1), 13,00%. Single Nucleotide Polymorphism (SNP) yang diperoleh sebanyak 13 situs. Sampel Kalimantan Barat memiliki dua SNP pada situs (471 dan 528). Kalimantan Selatan memiliki sembilan SNP (situs ke 120, 129, 144, 201, 306, 324, 474, 615 dan 644). Berdasarkan jarak genetik, perbedaan terbesar terletak pada sampel Kalimantan Selatan (1,58%) dibandingkan dengan Lampung dan Kalimantan Barat. Hasil rekonstruksi pohon filogenetik K2P neighbor-joining, menunjukkan bahwa sampel Kalimantan Selatan berada pada grup yang berbeda. Sampel Kalimantan Barat menunjukkan kekerabatan lebih dekat dengan grup Lampung.